Early presentation of pembrolizumab-associated pneumonitis. Issue 7 (15th July 2021) - Christy, Joshua; Rafae, Abdul; Kandah, Emad; Kunadi, Arvind
Abstract : Pembrolizumab is a selective anti-PD-L1 humanised monoclonal antibody approved by the Food and Drug Administration for treating multiple cancers, including cervical cancer, non-small cell lung cancer (NSCLC), renal cell carcinoma, bladder cancer, and squamous head and neck cancer. Pneumonitis is a rare but known complication of pembrolizumab treatment for NSCLC. The median time frame of its appearance is 2.8 months. However, we present a case of pneumonitis appearing within 48 hours. The patient presented with rapidly progressive respiratory failure, and imaging demonstrated diffuse bilateral patchy involvement of the upper lung lobe and pre-hilar regions, which likely indicate pneumonitis. Because of likely grade 3 pneumonitis, he was treated with steroids and showed immediate improvement of symptoms. Repeated CT imaging showed resolution of bilateral patchy infiltrates. He was discharged to the rehabilitation unit. Rapid recognition of pneumonitis as a side effect of pembrolizumab is important because early treatment can help prevent respiratory failure and possible death.